2017
DOI: 10.1007/s00432-016-2331-0
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine priming prior to low-dose chemotherapy improves patient outcomes in myelodysplastic syndromes-RAEB: a retrospective analysis vs. chemotherapy alone

Abstract: PurposeThe aim of this study was to examine whether decitabine priming prior to low-dose chemotherapeutic regimens could improve outcomes in patients with myelodysplastic syndromes—refractory anemia with excess of blasts (MDS-RAEB).MethodsThe current retrospective analysis included all MDS-RAEB patients receiving idarubicin/cytarabine (IA) or aclacinomycin/cytarabine (AA), with or without decitabine priming during a period from February 2010 to May 2015. Treatment response and toxicity were compared between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…DLI has been used as a type of allo-TLI for decades; however, non-ablative chemotherapy followed by HLA-mismatched stem cell transplantation, also referred to as “micro-transplantation”, has also been used to treat myeloid malignancies, with a better response, faster blood cell recovery, and lower TRM rate than conventional regimens, especially in elderly AML patients and patients with MDS ( 13 17 , 19 , 36 39 ). In these previous studies, although CD34 + hematopoietic stem cells were mobilized and isolated from HLA-mismatched donors and infused into the recipient, most researchers believed that the main functional anti-leukemia cells were T-cells, and donor CD3 + T-cells were found to interfere with survival after microtransplantation ( 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…DLI has been used as a type of allo-TLI for decades; however, non-ablative chemotherapy followed by HLA-mismatched stem cell transplantation, also referred to as “micro-transplantation”, has also been used to treat myeloid malignancies, with a better response, faster blood cell recovery, and lower TRM rate than conventional regimens, especially in elderly AML patients and patients with MDS ( 13 17 , 19 , 36 39 ). In these previous studies, although CD34 + hematopoietic stem cells were mobilized and isolated from HLA-mismatched donors and infused into the recipient, most researchers believed that the main functional anti-leukemia cells were T-cells, and donor CD3 + T-cells were found to interfere with survival after microtransplantation ( 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can reduce DNA methylation by inhibiting DNA methyltransferase, make the tumor suppressor gene return to normal, reactivate the gene inactivated due to DNA excessive methylation, and make the process of cell differentiation, aging or apoptosis return to normal. 16 , 17 A study of Ye et al enrolled 81 cases of MDS-RAEB, 18 40 patients were treated with decitabine before chemotherapy, and the median follow-up time was 10.9 months. Through comparing the results of chemotherapy alone with that of DAC before chemotherapy, it was found that the objective response rate (ORR) and CR rate of the decitabine group was significantly higher than that of chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…For the combination subgroup analysis, Studies using standard dose of intensive chemotherapy (DA, IA, etc.) [17][18][19][20] were classified as HMA + high-intensity subgroup, while those using reduced dose of intensive chemotherapy [21][22][23] were taken as HMA + low-intensity subgroup. Studies with compatible age and cytogenetic risk were first selected according to the median age.…”
Section: Study Selectionmentioning
confidence: 99%
“…The pooled CTCAE grade 3-4 infection rate was 66% (95%CI: 59%-73%) and 43% (95%CI: 0%-95%, P=0.000), and the pooled grade 3-4 cardiac rate was 12% (95%CI: 7%-16%) and 1% (95%CI: 0%-3%, P=0.000) for high and low-intensity subgroup, respectively. There was one study in each subgroup reporting grade 3-4 bleeding rate, which was 6% in high-intensity subgroup [17] and 28% for low-intensity subgroup [22].…”
Section: Subgroup Analysismentioning
confidence: 99%